Interventional Cryoneurolysis: What Is the Same, What Is Different, What Is New? - Bittman, Ross W.; Behbahani, Keywan; Gonzalez, Felix; Prologo, J. David (Seminars in Interventional Radiology, 2019)
Cryoneurolysis is the deliberate application of cold temperatures to nerves for therapeutic purposes. The idea of treating pain with this technique is thousands of years old and has evolved over time through the application of surgical techniques, nerve stimulation and/or landmark guidance, and through device development. Recent integration of the interventional radiology skill set to this space has unlocked a myriad of opportunities—primarily through a unique ability to percutaneously access deep structures in the body with accuracy and precision, and the capacity to monitor ablation zones. Understanding of the specific neurohistological process that follows targeted cryoneurolysis leads to new options for treating patients in pain without drugs and opens doors for the potential modification of a wide array of disease states.
Keywords: interventional; cryoneurolysis; cryoanalgesia; cryoablation